Answer:
(x, y) = (6, -7)
Step-by-step explanation:
Assuming you want to solve the equations for x and y, you can divide the second equation by 2 to get
x -2y = 20
then add 2y to obtain an expression for x:
x = 20 +2y
Substituting this into the first equation gives ...
5(20 +2y) +3y = 9
100 +13y = 9 . . . . . . eliminate parentheses, collect terms
13y = -91 . . . . . . . . . .subtract 100
y = -7 . . . . . . . . . . . . .divide by 13
Using this in our expression for x, we find ...
x = 20 +2(-7) = 6
The solution is (x, y) = (6, -7).